تأثير الحوسبة السحابية على ممارسة مهنة التدقيق - محمد فاتح محمد جميل; فيحاء عبدالخالق البكوع (PROSPECTIVE RESEARCHES, 2023)
The impact of cloud computing on the practice of the audit profession.The current century has been characterized by many stages of the process of enhancing information technology, and one of the models that has been adopted most quickly is cloud computing, which is one of the important technological models for information and communication technology due to its ability to develop and exploit infrastructure resources by providing computing resources as services, which caused a significant change. In the economics of information and communication technology, which had a great impact on the business and financial environment due to its various advantages, including helping auditors to perform their work faster and more accurately, in addition to the possibility of its development and what follows to benefit from this development. The research dealt with research methodology and previous studies in the field of research, then dealt with clarifying the integrated philosophy of what cloud computing is in terms of its inception, concept and benefits, cloud computing architecture and models of cloud computing, as well as the disadvantages and risks of cloud computing, then the research dealt with practicing the profession of auditing in the cloud computing environment.